Antioxidant properties of fermented soymilk and its anti-inflammatory effect on DSS-induced colitis in mice - Sun, Yijiao; Xu, Jingting; Zhao, Huiyan; Li, Yue; Zhang, Hui; Yang, Baichong; Guo, Shuntang (Frontiers in Nutrition, 2023)
Lactic acid-fermented soymilk as a new plant-based food has aroused extensive attention because of its effects on nutrition and health. This study was conducted to delve into the antioxidative and anti-inflammatory activities of lactic acid-fermented soymilk. To elucidate the key factors that affect the antioxidant properties of fermented soymilk, the strains and preparation process were investigated. Findings show that the fermented soymilk prepared using hot-water blanching method (BT-80) demonstrated a better antioxidant activity than that using conventional method (CN-20). Besides, a huge difference was observed among the soymilks fermented with different strains. Among them, the YF-L903 fermented soymilk demonstrated the highest ABTS radical scavenging ability, which is about twofold of that of unfermented soymilk and 1.8-fold of that of L571 fermented soy milk. In vitro antioxidant experiments and the analysis of H2O2-induced oxidative damage model in Caco-2 cells showed that lactic acid-fermentation could improve the DPPH radical scavenging ability, ABTS radical scavenging ability, while reducing the content of reactive oxygen species (ROS) and malondialdehyde (MDA) in Caco-2 cells induced by H2O2, and increasing the content of superoxide dismutase (SOD). Consequently, cells are protected from the damage caused by active oxidation, and the repair ability of cells is enhanced. To identify the role of fermented soymilk in intestinal health, we investigate its preventive effect on dextran sodium sulfate-induced colitis mouse models. Results revealed that the fermented soymilk can significantly improve the health conditions of the mice, including alleviated of weight loss, relieved colonic injury, balanced the spleen-to-body weight ratio, reduced the disease index, and suppressed the inflammatory cytokines and oxidant indexes release. These results suggest that YF-L903 fermented soymilk is a promising natural antioxidant sources and anti-inflammatory agents for the food industry. We believe this work paves the way for elucidating the effect of lactic acid-fermented soymilk on intestinal health, and provides a reference for the preparation of fermented soymilk with higher nutritional and health value.